Examination of a complementary set of spiritual assessment tools for LDS clients. Issue 9 (26th November 2018) - Limb, Gordon Earl; Hodge, David; Ward, Peter; Alboroto, Richard; Larkin, Zachary
ABSTRACT: The importance of providing culturally competent services has been promoted in the social work profession. With the Latter-day Saints (LDS) Church being the fourth largest and one of the faster growing churches in the United States, it is important for social workers to have an evidence-based, working knowledge of how to help members of this religious group. Utilising a mixed method approach, this study examined a complementary set of spiritual assessment tools by looking at five instruments' level of cultural consistency, strengths, and limitations. Overall, results showed that each of the five spiritual assessment tools were congruent with LDS culture and if appropriately administered could help social workers provide appropriate and effective services that incorporate religion and spirituality. Results of this mixed method study offer an important step at providing evidence-based spiritual assessment tools for social workers seeking to provide culturally competent services to LDS clients.